La dépossession. Réformes, enseignement supérieur et pouvoirs au Maghreb - Ahmed Ghouati (Revue des Mondes Musulmans et de la Méditerranée)
As a part of the Lisbon economic strategy, the Bologna process has been driven from its inception by the European Commission. The charge of its enforcement has been thereafter given to the member States of the European Union, through the power of experts. The process has empowered the Commission at the expense of the nation-States, especially regarding education reforms. However, this institutional steering mode has been applied to three North African countries, as the Bologna process was extended. The European and North African leaders have officially praised the process, although the students and the teachers did not support its institutional aims. After describing the process’ appropriation mode, we will outline the results of a survey conducted between November 2007 and May 2008 among scholars (N=125). Our hypothesis is that, while the Bologna process is part of a global economical dynamic, it is however concretized by local powers in a logic of dispossession and/or domination, at the expense of local societies.